Journalistic role performance in times of COVID (2023)
This paper examines journalistic role performance in coverage of the COVID-19 pandemic, based on a content analysis of newspaper, television, radio and online news in 37 countries. We test a set of hypotheses derived from two perspectives on the role of journalism in health crises. Mediatization theories assume that news media tend to sensationalize or to politicize health crises. A contrasting perspective holds that journalists shift toward more deferential and cooperative stances toward health and political authorities in a health crisis, attempting to mobilize the public to act according to the best science. Hypotheses derived from these perspectives are tested using the standard measures of journalistic roles developed by the Journalistic Role Performance Project. Results show that the deference/cooperation/consensus perspective is better supported, with media moving away from the Watchdog and Infotainment, and toward performance of the Service and Civic roles. We also explore differences in the pattern by country.